Brand protection and the global risk of product counterfeits : a total business solution approach - Wilson, Jeremy M. (Edward Elgar Publishing, 2022)
"Product counterfeits and other brand infringements represent a growing and substantial risk to firms, consumers, and society. While policing such illicit activity is important, there is much that firms can do to protect themselves and their customers. Grounded in field research and practice, this book presents a total business solution approach to brand protection that enables firms to prevent infringement from occurring and to respond efficiently when it does. This total business solution provides a framework for building and advancing brand protection programs that are strategic, comprehensive, and evidence based. Coupling perspectives and illustrations from several academic disciplines and industries, this book serves as a road map or blueprint for companies to develop and implement a proactive strategy to protect their brands. It serves as a guide to help firms to continuously learn, innovate, and efficiently allocate resources in a way that maximizes brand protection performance. Graduate and executive education programs and scholars in business, law, and criminal justice will benefit from adopting Brand Protection and the Global Risk of Product Counterfeits as course reading, research, or a valued addition to their personal library. Brand protection practitioners in firms large and small, working in brand protection, security, supply chain, legal, quality assurance, packaging, C-suite, marketing, sales, and related areas will find this book essential in helping them to develop a roadmap for establishing a robust brand protection program and to take their existing brand protection to the next level of effectiveness and efficiency"--